DAMPAK HUKUM DELIMITASI PERBATASAN LAUT TERITORIAL YANG BELUM SELESAI ANTARA INDONESIA DENGAN MALAYSIA DI TANJUNG DATU TERHADAP KEGIATAN PENANGKAPAN IKAN MASYARAKAT SETEMPAT - NIM. A1011201297, PANCA NUR AZMI FEBRIANTO (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This study discusses the legal implications of the unresolved delimitation of the territorial sea boundary between Indonesia and Malaysia in Tanjung Datu on fishing activities conducted by the local community. The aim of this research is to analyze the legal impacts arising from the unresolved delimitation of the territorial sea boundary between Indonesia and Malaysia in Tanjung Datu from the perspective of international maritime law, as outlined in the 1982 United Nations Convention on the Law of the Sea (UNCLOS). It also seeks to examine the legal status of fishing activities conducted by the local community in the Tanjung Datu area. The conflict stemming from this issue creates legal uncertainty that affects the activities of fishermen from both countries, including the potential for illegal fishing. This uncertainty can lead to the criminalization of fishermen due to the ambiguous legal status of fishing activities resulting from the unresolved delimitation of the territorial sea boundary in the Tanjung Datu region. The research employs a normative legal research method, as it focuses on examining the applicable laws and regulations relevant to the research topic. Based on the analysis, the legal impact of the unresolved territorial sea boundary delimitation has resulted in the area being classified as a disputed sea (status quo), referred to as a